FAKTOR YANG MEMILIKI PENGARUH TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN DI BEI - Sumanta, Sandy Irmawan; Wijaya, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The aim of this research is to identify the factors that can influence tax avoidance. In this study several contributing variables are profitability, leverage, and company size. The companies selected for this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. Then, for sample selection, we chose a targeted extraction method that also matched the data selection criteria, and finally collected 22 companies. The data processing statistical program used to process the data in this study is SPSS version 22. The results of this study indicate that profitability has no effect on tax avoidance, but leverage and firm size have a positive effect on tax avoidance.